Comparative effectiveness and safety of direct-acting oral anticoagulants (DOACS) for the reduction of recurrent venous thromboembolism in cancer patients: A protocol for systematic review and network meta-analysis using a generalized pairwise modeling methodology - Danjuma, Mohammed ibn-Mas’ud (Medicine (Baltimore), 2020)
BACKGROUND: There has been a significant improvement in both our understanding and therapeutic choices available to clinicians for the management of cancer associated thrombosis (CAT). Even with the recent publication of a systematic review and landmark trials demonstrating the non-inferiority of DOACS-based anticoagulation strategy compared to the standard of care in patients with CAT, there is unresolved uncertainty regarding the exact hierarchy of risks and effectiveness of various DOAC analogues in these cohorts of patients. METHOD: We will carry out a network meta-analyses, utilizing a novel generalized pairwise methodology to generate direct and indirect comparisons between the various DOAC analogues. We will search the following databases for studies that satisfies pre-specified inclusions criteria; these include PubMed, EMBASE, Cochrane library, Clinicaltrials.gov, conference abstracts among other sources. The primary efficacy and safety outcomes are recurrent VTE and major hemorrhagic events, respectively. Two reviewers will Search the databases independently with the view to identify studies that meet eligibility criteria. The methodological quality of the included studies will be determined using a recently validated risk of bias assessment tool. RESULTS: We expect that the result of this review will ascertain the hierarchy of risks and effectiveness of various DOAC analogues in patients with CAT. CONCLUSION: Results of this review will assist in informed decisions making regarding therapeutic guidelines of DOAC in CAT.